Eyring-powell hybrid nanofluid with radiative heat flux: Case over a shrinking sheet - Aljabali, Ahlam; Abdul Rahman, Mohd Kasim; Najiyah Safwa, Khashi’ie; Iskandar, Waini; Noor Amalina Nisa, Ariffin (Semarak Ilmu Publishing, 2023)
This study investigates the radiative heat flux effect on Eyring-Powell hybrid nanofluid together with analysis thermal passing towards a shrinking sheet containing nanoparticles. The proposed mathematical model respected to the boundary condition is converted to the similarity equations by adopting the suitable transformations. In order to reduce the complexity of model, the similarity equations are then computed by applying the bvp4c function in MATLAB software. Outcomes reveal the thermal performance is upgraded in dispersing the nanoparticle to the base fluid, and it is marked under hybrid nanoparticles consideration. The presence of Eyring-Powell, radiation and shrinking parameters are the controller parameter in regulatory the sheer stress and thermal performance of the fluid. Ag − MgO.